Fórmulas diretas de Ansheles - Salgado, Eduardo A. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1960)
The "direct formulas" by Professor Ansheles, a Russian crystallographer, are published, without deduction, in the Crystallography by BOLDYREV, (1934), translated into Spanish by Candel Vila. In the present work the author deduces such formulas, using the stereographic projection.